Effects of Iodonium Analogs on Nadph Oxidase 1 in Human Colon Cancer Cells - Krishnendu K. Roy; Jiamo Lu; James H. Doroshow (MDPI AG, 2021)
Recent studies suggest that of the molecules postulated to function as inhibitors of the NADPH oxidase family of enzymes iodonium analogs known to broadly interfere with flavin dehydrogenase function demonstrate mechanistic validity as NADPH oxidase poisons. In recent work, we have produced a series of novel iodonium compounds as putative inhibitors of these oxidases. To evaluate the potential utility of two novel molecules with favorable chemical properties, NSC 740104 and NSC 751140, we compared effects of these compounds to the two standard inhibitors of this class, diphenyleneiodonium and di-2-thienyliodonium, with respect to antiproliferative, cell cycle, and gene expression effects in human colon cancer cells that require the function of NADPH oxidase 1. Both new agents blocked NADPH oxidase-related reactive oxygen production, inhibited tumor cell proliferation, produced a G1/S block in cell cycle progression, and inhibited NADPH oxidase 1 expression at the mRNA and protein levels at low nM concentrations in a fashion similar to or better than the parent molecules. These studies suggest that NSC 740104 and NSC 751140 should be developed further as mechanistic tools to better understand the role of NADPH oxidase inhibition as an approach to the development of novel therapeutic agents for colon cancer.